Solar-assisted single-double-effect absorption chiller for use in Asian tropical climates. (December 2016) - Lubis, Arnas; Jeong, Jongsoo; Saito, Kiyoshi; Giannetti, Niccolo; Yabase, Hajime; Idrus Alhamid, Muhammad; Nasruddin,
Abstract: Solar energy is accessible throughout the year in tropical regions. The latest development of absorption chillers has demonstrated that these systems are suitable for effective use of solar energy. The utilisation of solar energy for heat-driven cooling systems has significant advantages. Without a doubt, solar energy represents a clean energy source that is available without any additional fuel cost, and that can be proportionally accessible when the cooling load increases during the middle hours of the day. This study focuses on a single-double-effect absorption chiller machine that was installed in Indonesia. The system is driven by a dual-heat source that combines gas and solar energy. This system is characterised by simulating its performance in various conditions in terms of the cooling water (28–34 °C) and the hot water (75–90 °C) inlet temperatures. The reference operating condition of this system is 239 kW of cooling capacity. The mathematical model is validated and shows a good agreement with experimental data. In the operative range considered, simulation results yield a coefficient of performance between 1.4 and 3.3, and a gas reduction ratio from 7 to 58% when compared to a double-effect absorption chiller driven by gas. Based on the simulation results, this system is expected to have a good potential for widespread use in tropical Asia regions. Highlights: The single-double-effect absorption chiller is driven by gas and solar energy. The system can work either as a single-effect or as a single-double–effect system. Steady analysis is used to characterise the system performance. Potential energy saving up to 58%. The system is expected to have a good potential for use in tropical Asia regions.